La critica dantesca di Fortini - Carrai, Stefano (L’ospite ingrato, 2021)
The paper is focused on Fortini’s point of view on Dante’s poetry, from the early review of Contini’s edition of Dante’s Rime to the late essay on his metric. Fortini’s critics on Dante is always sensible to the problem of popularization, but also to the peculiar form of Dante’s texts, especially in the last essay on metric, not by chance part of an educational context.